Implementing Physical Learning Based On Momentum and Impulse Stem Materials to Develop Collaboration Skills - Yulianti, Dwi; Anjani, Dewi (Jurnal Ilmu Pendidikan, 2019)
The challenges of the 21st-century life require that every individual must master 21st-century skills. The 21st-century learning and innovation (4C) skills are among the skills that rank first among other skills. Collaboration skills are part of 4C skills that are important for students to develop. The 2013 curriculum policy and STEM-based learning are solutions to the challenges of the 21st-century development. The results of a survey of 16 high schools in the city of Semarang, show that schools have not applied to learn with the STEM approach and have not specifically developed collaboration skills. The purpose of this study is to investigate the development of student collaboration skills through the application of STEM-based physics learning. The research method used was quasi experimental with a form of nonequivalent control group design. The subjects of this study were students of class X MIPA SMA 11 Semarang, class X MIPA 5 as an experimental class, and class X MIPA 7 as a control class. Retrieval of data using observation and documentation methods. Analysis of research data using observation sheet analysis with the help of SPSS and Microsoft Office Excel programs. The results showed that collaboration skills after applying STEM-based physics learning developed in the medium category.